Psychometric properties of the Brazilian version of the Cognitive Emotion Regulation Questionnaire - Schäfer,Julia Luiza (2018)
Abstract Introduction: The Cognitive Emotion Regulation Questionnaire (CERQ) was developed to measure nine cognitive strategies referring to what someone thinks after the experience of threatening or stressful events. The main purpose of this study was to evaluate the validity of the Brazilian version of the CERQ. Methods: The adaptation process included translation, backtranslation, expert committee evaluation, and test on 30 participants from the target population. A sample of 445 university students completed the Portuguese version of the CERQ, a sociodemographic questionnaire, the Life Events Checklist (LEC-5), and the Positive and Negative Affect Schedule (PANAS) on an on-line research platform. Validity was assessed through confirmatory factor analysis of two models - a nine-factor model and a second-order model. Internal consistency was assessed through Cronbach's alpha analysis and correlations with affective variables measured by the PANAS. Results: The analyses showed that the nine-factor model of the CERQ has good factorial validity and high reliability, with Cronbach's alpha values ranging between 0.71 and 0.88. The second-order model did not have a good fit to the data. Conclusion: The results obtained in this study are similar to the ones found previously, indicating that the Brazilian version of the CERQ is a valid and reliable tool for assessing cognitive emotion regulation strategies, but that grouping them according to their adaptability is not recommended.